Effects of the open lung concept following ARDSnet ventilation in patients with early ARDS. Issue 1 (December 2015) - Rotman, Vivian; Carvalho, Alysson; Rodrigues, Rosana; Medeiros, Denise; Pinto, Eduardo; Bozza, Fernando; Carvalho, Carlos
Abstract Background Ventilation with low tidal volume (VT ) is well recognized as a protective approach to patients with acute respiratory distress syndrome (ARDS), but the optimal level of positive end-expiratory pressure (PEEP) remains uncertain. This study aims to evaluate two protective ventilatory strategies sequentially applied in patients with early ARDS. Methods In this prospective cohort study, fifteen patients were ventilated during 24 h with positive end-expiratory pressure (PEEP) adjusted according to the ARDSnet low-PEEP table (ARDSnet-24 h). During the next 24 h, nine patients with PaO2/FIO2 ratio below 350 mmHg were ventilated with PEEP titrated according to the Open Lung Concept protocol (ARDSnet + OLC). In the other six patients, regardless of their PaO2/FIO2 ratio, the ARDSnet remained for a further 24 h (ARDSnet-48 h). Ventilatory variables, arterial blood-gas and cytokine were obtained at baseline, 24 and 48 h. Additionally, whole-lung-computed tomography was acquired at 24 and 48 h. Results A sustained improvement in PaO2/FIO2 ratio (P = 0.008) with a decrease in collapsed regions (P = 0.008) was observed in the ARDSnet + OLC group compared with the ARDSnet-24 h group. A reduction in IL-6 in plasma (P < 0.02) was observed throughout the protocol in the ARDSnet + OLC group. Compared with the ARDSnet-48 h group, the ARDSnet + OLC presented smaller amounts of collapsed areas (P = 0.018) without significant differences in hyperinflated regions and in driving and plateau pressures. Conclusions In this set of patients with early ARDS, mechanical ventilation with an individually tailored PEEP sustained improved pulmonary function with better aeration, without significant increase in hyperinflated areas". Trial registration Brazilian Clinical Trials Registry (ReBec). RBR-5zm9pr. 04th November 2015